Placement of technological equipment on the basic chassis of the mobile transportation and reloading rope complex - Lagerev A.V; Tarichko V.I.; Lagerev I.A. (Научно-технический вестник Брянского государственного университета)
Mobile rope systems designed to carry out loading and unloading and transport and transfer operations in noequipped or hard-to-reach areas and ensuring the prompt deployment of the necessary technological means are a promising type of lifting and transport equipment. The article deals with the layout of the main technological equipment of one of the constructive variants of a mobile rope system on a base multi-axle wheeled chassis of high carrying capacity and performance. A variant of the layout with the central location of the end tower attachment point for supporting the leading rope pulley with a carrying rope on the base chassis frame is considered. Mathematical models have been developed that ensure the kinematic and power analysis of the kinematic scheme of the hydraulic mechanism for installing and fixing the end tower. The analysis of the influence of the main structural dimensions of the indicated mechanism on the dimensions of the mobile rope complex in the transport position, as well as on the force factors arising during the operation of the rope system is carried out. The necessary conditions have been established that must be met when designing a rope system to ensure the regulatory requirements for the movement of a mobile complex on automobile roads of the general using. The conditions for the location and length of the drive hydraulic cylinder of the end tower, which ensure the necessary movement of the tower from the transport position to the working position, have been established and analyzed; the presence of a significant zone of inadmissible location of the hinged assembly for attaching the hydraulic cylinder rod to the metal structure of the end tower has been revealed.